Legal Protection of the Moral Rights of National Film Creators Uploaded Without Permission on TikTok Social Media - Talaperuw, Vivi; Narwadan, Theresia Nolda Agnes; Labetubun, Muchtar Anshary Hamid (TATOHI: Jurnal Ilmu Hukum, 2025)
Introduction: The development of technology in this era has certainly made many platforms created, one of which is TikTok. Film is one of the copyrighted works that is included in the category of cinematographic works protected by Law Number 28 of 2014 concerning Copyright. On this platform, users can upload a variety of content from the results of user creativity.Purposes of the Research: Analyzing the legal protection of the moral rights of national film creators uploaded without permission on TikTok social media.Methods of the Research: The research method used is normative research, statutory approach, primary and secondary legal materials and material collection procedures using literature studies. the approaches used are: statute approach, conceptual approach, and casus approach. The technique of searching for legal materials uses document study techniques, and analyzes the study using qualitative analysis.Findings of the Research: Research shows that protection related to the moral rights of national film creators uploaded on the TikTok application without the creator's permission is by providing sanctions to violators as contained in Law Number 28 of 2014 concerning Copyright and related to the settlement of moral rights disputes for national film creators uploaded without permission can be done in two ways, namely litigation and non-litigation.  For the litigation route, the dispute can be resolved in court, while for non-litigation, the settlement can be through alternative dispute resolution which includes mediation, conciliation and negotiation and the most effective settlement in this problem is through the litigation route so that it can have a deterrent effect.